OPTIMASI SUHU DAN WAKTU REAKSI PADA PEMBUATAN SABUN PADAT DARI MINYAK JELANTAH SAWIT SEBAGAI UPAYA CIRCULAR ECONOMY - -, Cengristitama; Sari, Myra Wardati; Firmansyah, Muhammad Faishal (Jurnal TEDC; Vol 19 No 3 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i3.1410, 2025)
Used palm oil is a type of household waste that has potential to pollute the environment if not managed properly. This study aims to optimize the temperature and reaction time in the production of solid soap from used palm oil through the saponification process. The temperatures used were 60 °C, 70 °C, and 80 °C, with reaction times of 60, 70, and 80 minutes. The soap quality analysis included water content, free alkali content, pH, and saponification number, which were compared with the SNI 06-3532-1994 and SNI 3532-2021 solid soap quality standards. The result showed that the optimum conditions were obtained at a temperature of 70 °C and a reaction time of 60 minutes, with a moisture content of 8.6%, free alkali content of 0.045%, pH of 9.4, and saponification number of 256.2 mg KOH/g. These conditions comply with SNI standards and support the principles of the circular economy through the utilization of waste into value-added products.